Before-After Study of an Electronic Order Set for Reversal of Vitamin K Antagonist–Associated Intracerebral Hemorrhage. (January 2018) - Vitt, Jeffrey R.; Do, Lynn V.; Shah, Nirav H.; Fong, Gary; Nguyen, Nicole Y.; Kim, Anthony S.
Background: Vitamin K antagonist (VKA)–associated intracerebral hemorrhages (ICHs) are more likely to expand and are associated with higher mortality than primary ICH. Prompt reversal of anticoagulant effect with prothrombin complex concentrate (PCC) may promote hemostasis and decrease hematoma expansion. The aim of this study was to evaluate the impact of an electronic order set designed to standardize and facilitate more timely reversal of coagulopathy in VKA-associated ICH. Methods: We identified all adults who received PCC for VKA-associated ICH from June 2012 to June 2015 at University of California San Francisco Medical Center, which included a period before and after an electronic order set became available in 2014. We abstracted baseline demographics and clinical data from electronic health records. The primary outcome was time from radiographic identification of ICH to administration of PCC. Results: Thirty-one patients received PCC for VKA-associated ICH, including 17 patients before and 14 patients after the order set became available. Baseline demographics and clinical features were similar. Order set use was associated with a significant decrease in the time from identification of ICH on imaging to the administration of PCC (median 83 vs 45 minutes; P = .02), more accurate dosing (29.4% vs 92.9%; P < .01), and a shorter time from the PCC order to follow-up international normalized ratio (INR) testing (median 164 vs 85 minutes, P = .001). Conclusion: An electronic order set for administering PCC for VKA-associated ICH was associated with significantly faster time to PCC administration and increased dosing accuracy.